2395. Mechanism-Based-Susceptibility Testing (MBST) Using Disc Diffusion Assays (DDA) to Guide Treatment of Multidrug- and Extensively Drug-Resistant Pseudomonas aeruginosa (MDR-XDR-Pa) in a Cystic Fibrosis (CF) Lung Transplant Recipient; Are We Ready for Combination Therapy vs. MDR-XDR-Pa?. (26th November 2018) - Abbo, Lilian M; Yasmin, Mohamad; Marshall, Steven H; Perez, Federico; Corzo-Pedrosa, Mónica; Camargo, Jose F; Simkins, Jacques; Aragon, Laura; Anjan, Shweta; Morris, Michele I; Brozzi, Nicolas; Loebe, Mathias; et al.
Abstract: Background: Lung infections with MDR-XDR-Pa in patients with CF are challenging due to the emergence of antibiotic resistance. We applied MBST with DDA to guide combination antibiotic therapy in an 18-year-old woman with CF. We investigated if this approach can assist in choosing effective regimens. Methods: Consecutive Pa respiratory isolates were collected between 12/16 and 3/18 and typed with MLST. After automated antibiotic susceptibility (AST) and Kirby-Bauer testing, we performed double or triple DDAs. Combinations were based on mechanisms (MBST) of anti-pseudomonal antibiotics (e.g., targeting of penicillin-binding proteins, β-lactamase inhibition, and cell membrane disruption). Results: During therapy, 1859 antibiotic-days were administered. Fifteen Pa isolates, (9 sequence type (ST) 2100 and 1 ST463) with varying AST patterns were found (figure). MBST with DDA revealed active combinations for isolates resistant to individual antibiotics (table). These combinations led to a microbiological response permitting lung transplantation. Antibiotic regimens were also informed by allergies, clinical and radiologic findings. Conclusion: Strains with evolving resistance profiles recapitulate the dynamic nature of respiratory infections in CF. Double or triple DDAs identified potential treatment options, e.g., vs. MDR-XDR Pa . MBST can support the management of challenging infections. Table: Antimicrobial combinations reflecting zones of inhibition by strain and date. CZA: ceftazidime–avibactam; C/T: ceftolozane-tazobactam; TOB: tobramycin; PMB: polymyxin B; FOF: fosfomycin; TZP: piperacillin–tazobactam; CIP: ciprofloxacin; IPM: imipenem; MEM: meropenem. Bold: largest zone Disclosures: L. M. Abbo, Roche Diagnostics: Scientific Advisor, Consulting fee. M. I. Morris, Chimerix: Investigator and Scientific Advisor, Consulting fee and Research support. Merck: Investigator, Research grant.